Pilar Chías Navarro. (2022). Amoenitas loci, paupertas, caritas. La arquitectura de la Universidad de Alcalá, hipótesis gráficas sobre la fundación de Cisneros. Alcalá: Universidad de Alcalá (diségno, 2023)
The book Amoenitas loci, paupertas, caritas. La arquitectura de la Universidad de Alcalá, hipótesis gráficas sobre la fundación de Cisneros, by Dr. Pilar Chías Navarro, suggests to ricreate the lost image of the original architecture of theUniversitas Complutensis, founded by Cardinal Cisneros in 1499. The author’s proposal focuses on the reconstruction of the foundational nucleus, the so-called Manzana Cisneriana, whose construction began in March 1499 withthe building of the Colegio Mayor San Ildefonso, a month before the Carta bulada Inter Caetera was granted on 13 April of the same year. [read more]